Anti- or profibrillatory effects of Na+ channel blockade depend on the site of application relative to gradients in repolarization - Coronel, Ruben; Wilms-Schopman, Francien; Janse, Michiel (Frontiers in Physiology, 2010)
Introduction. Sodium channel blockers are associated with arrhythmic sudden death, although they are considered antiarrhythmic agents. The mechanism of these opposing effects is unknown. Methods. We used a model of induction of ventricular fibrillation (VF) based on selective perfusion of the vascular beds of isolated porcine hearts (n=8). One bed was perfused with sotalol (220 µM), the adjacent bed with pinacidil (80 µM), leading to repolarization heterogeneity (late repolarization in the sotalol-, early in the pinacidil-area). Premature stimulation from the area with the short action potential was performed. Epicardial activation/repolarization mapping was done. Results. In 3 of the 8 hearts VF was inducible prior to infusion of flecainide. In those hearts the Fibrillation Factor (FF), the interval between the last activation of the premature beat (S2) in the late repolarizing (sotalol) domain and the earliest S2 repolarization in the early repolarizing (pinacidil) domain, was significantly shorter than in the hearts without VF (33+/-22 vs 93+/-11 ms, m+/-SEM, p<0.05). In the 3 hearts with VF flecainide was infused in the pinacidil domain after defibrillation. This led to shortening of the line of block, local delay of S2 activation and repolarization, an increase in FF and failure to induce VF. In the 5 hearts without VF, flecainide was subsequently infused in the sotalol domain. This led to a local delay of S2 activation, a shortening of FF (by 47+/- 3 ms) and successful induction of VF in 3 hearts. In the 2 remaining hearts FF did not decrease enough (maximally 13 ms) to allow reentry. Conclusions Sodium channel blockade applied to myocardium with a short refractory period is antifibrillatory whereas sodium channel blockade of myocardium with a long refractory period is profibrillatory. Our study provides a mechanistic basis for pro- and anti-arrhythmic effects of sodium channel blockers in the absence of structural heart disease.